PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP DISIPLIN BELAJAR SISWA KELAS X SMA HANDAYANI PEKANBARU T.P 2014/2015 - Destry Wita; Raja Arlizon; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study purpose to know learn dicipline students before and after group tuition and to know how big influence of Tuition group to discipline learn Class student at class X SMA Handayani Pekanbaru academic year 2014/2015. problem is, 1)Determine level of learn discipline before tuition grup. 2) Determaine proses of tuition group with student learn discipline. 3) Determine effect of student learn discipline after tuition group. 4) To know the different learn discipline before and after tuition group. 5) To know effect level of student learn discipline with tuition group.The method used in the study was quasi experimental, quasi experimental studies in which no treatment was the dependent variable. Subjects of this study and the sample totaled 206 sudents were taken by random sampling technique were 30 samples from students of class X SMA Handayani Pekanbaru. The results of the data analysis that the appointment of acquisition is greater than t table t at 5%, = 2.000 (11,405> 2.000) , Ho is rejected and Ha accepted, which means that there are differences in the study significantly between student discipline before and after the implementation of group tuition services in class X SMA Handayani Pekanbaru of 38%.Keywords: group tuition, disciplinary learning, students